Characterization and miRNA Profiling of Extracellular Vesicles from Human Osteoarthritic Subchondral Bone Multipotential Stromal Cells (MSCs). (9th October 2021) - Sanjurjo-Rodríguez, Clara; Crossland, Rachel E.; Reis, Monica; Pandit, Hemant; Wang, Xiao-nong; Jones, Elena
Abstract : Osteoarthritis (OA) is a heterogeneous disease in which the cross-talk between the cells from different tissues within the joint is affected as the disease progresses. Extracellular vesicles (EVs) are known to have a crucial role in cell-cell communication by means of cargo transfer. Subchondral bone (SB) resident cells and its microenvironment are increasingly recognised to have a major role in OA pathogenesis. The aim of this study was to investigate the EV production from OA SB mesenchymal stromal cells (MSCs) and their possible influence on OA chondrocytes. Small EVs were isolated from OA-MSCs, characterized and cocultured with chondrocytes for viability and gene expression analysis, and compared to small EVs from MSCs of healthy donors (H-EVs). OA-EVs enhanced viability of chondrocytes and the expression of chondrogenesis-related genes, although the effect was marginally lower compared to that of the H-EVs. miRNA profiling followed by unsupervised hierarchical clustering analysis revealed distinct microRNA sets in OA-EVs as compared to their parental MSCs or H-EVs. Pathway analysis of OA-EV miRNAs showed the enrichment of miRNAs implicated in chondrogenesis, stem cells, or other pathways related to cartilage and OA. In conclusion, OA SB MSCs were capable of producing EVs that could support chondrocyte viability and chondrogenic gene expression and contained microRNAs implicated in chondrogenesis support. These EVs could therefore mediate the cross-talk between the SB and cartilage in OA potentially modulating chondrocyte viability and endogenous cartilage regeneration.